Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the inequality [tex]\(3 x^2 + 5 x > -2\)[/tex], we can follow these steps:
1. Rewrite the inequality:
[tex]\[ 3 x^2 + 5 x + 2 > 0 \][/tex]
This inequality is now a quadratic inequality.
2. Find the roots of the quadratic equation [tex]\(3 x^2 + 5 x + 2 = 0\)[/tex]:
To do this, we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a = 3\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(c = 2\)[/tex].
First, calculate the discriminant ([tex]\(\Delta\)[/tex]):
[tex]\[ \Delta = b^2 - 4ac = 5^2 - 4 \cdot 3 \cdot 2 = 25 - 24 = 1 \][/tex]
The discriminant is 1, which is positive, indicating two real and distinct roots.
Hence, the roots are:
[tex]\[ x = \frac{-5 \pm \sqrt{1}}{2 \cdot 3} = \frac{-5 \pm 1}{6} \][/tex]
Thus, the roots are:
[tex]\[ x = \frac{-5 + 1}{6} = \frac{-4}{6} = -\frac{2}{3} \][/tex]
and
[tex]\[ x = \frac{-5 - 1}{6} = \frac{-6}{6} = -1 \][/tex]
3. Determine the sign of [tex]\(3 x^2 + 5 x + 2\)[/tex] in the intervals determined by the roots:
The roots [tex]\(-1\)[/tex] and [tex]\(-\frac{2}{3}\)[/tex] divide the number line into three intervals: [tex]\((-\infty, -1)\)[/tex], [tex]\((-1, -\frac{2}{3})\)[/tex], and [tex]\((-\frac{2}{3}, \infty)\)[/tex].
- For [tex]\(x \in (-\infty, -1)\)[/tex]: Choose [tex]\(x = -2\)[/tex]:
[tex]\[ 3(-2)^2 + 5(-2) + 2 = 12 - 10 + 2 = 4 > 0 \][/tex]
- For [tex]\(x \in (-1, -\frac{2}{3})\)[/tex]: Choose [tex]\(x = -\frac{3}{4}\)[/tex]:
[tex]\[ 3\left(-\frac{3}{4}\right)^2 + 5\left(-\frac{3}{4}\right) + 2 = 3 \cdot \frac{9}{16} - \frac{15}{4} + 2 = \frac{27}{16} - \frac{60}{16} + \frac{32}{16} = -\frac{1}{16} < 0 \][/tex]
- For [tex]\(x \in (-\frac{2}{3}, \infty)\)[/tex]: Choose [tex]\(x = 0\)[/tex]:
[tex]\[ 3(0)^2 + 5(0) + 2 = 2 > 0 \][/tex]
4. Combine the intervals where the quadratic expression is positive:
From the above analysis:
- [tex]\(3 x^2 + 5 x + 2 > 0\)[/tex] in the intervals [tex]\((-\infty, -1)\)[/tex] and [tex]\((-\frac{2}{3}, \infty)\)[/tex].
5. Write down the solution in interval notation:
[tex]\[ x \in (-\infty, -1) \cup (-\frac{2}{3}, \infty) \][/tex]
6. Identify the corresponding option:
The correct solution matches the first option: [tex]\(x <-1\)[/tex] or [tex]\(x > -\frac{2}{3}\)[/tex].
Thus, the solution to the inequality [tex]\(3 x^2 + 5 x > -2\)[/tex] is:
[tex]\[ x < -1 \text{ or } x > -\frac{2}{3} \][/tex]
1. Rewrite the inequality:
[tex]\[ 3 x^2 + 5 x + 2 > 0 \][/tex]
This inequality is now a quadratic inequality.
2. Find the roots of the quadratic equation [tex]\(3 x^2 + 5 x + 2 = 0\)[/tex]:
To do this, we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\(a = 3\)[/tex], [tex]\(b = 5\)[/tex], and [tex]\(c = 2\)[/tex].
First, calculate the discriminant ([tex]\(\Delta\)[/tex]):
[tex]\[ \Delta = b^2 - 4ac = 5^2 - 4 \cdot 3 \cdot 2 = 25 - 24 = 1 \][/tex]
The discriminant is 1, which is positive, indicating two real and distinct roots.
Hence, the roots are:
[tex]\[ x = \frac{-5 \pm \sqrt{1}}{2 \cdot 3} = \frac{-5 \pm 1}{6} \][/tex]
Thus, the roots are:
[tex]\[ x = \frac{-5 + 1}{6} = \frac{-4}{6} = -\frac{2}{3} \][/tex]
and
[tex]\[ x = \frac{-5 - 1}{6} = \frac{-6}{6} = -1 \][/tex]
3. Determine the sign of [tex]\(3 x^2 + 5 x + 2\)[/tex] in the intervals determined by the roots:
The roots [tex]\(-1\)[/tex] and [tex]\(-\frac{2}{3}\)[/tex] divide the number line into three intervals: [tex]\((-\infty, -1)\)[/tex], [tex]\((-1, -\frac{2}{3})\)[/tex], and [tex]\((-\frac{2}{3}, \infty)\)[/tex].
- For [tex]\(x \in (-\infty, -1)\)[/tex]: Choose [tex]\(x = -2\)[/tex]:
[tex]\[ 3(-2)^2 + 5(-2) + 2 = 12 - 10 + 2 = 4 > 0 \][/tex]
- For [tex]\(x \in (-1, -\frac{2}{3})\)[/tex]: Choose [tex]\(x = -\frac{3}{4}\)[/tex]:
[tex]\[ 3\left(-\frac{3}{4}\right)^2 + 5\left(-\frac{3}{4}\right) + 2 = 3 \cdot \frac{9}{16} - \frac{15}{4} + 2 = \frac{27}{16} - \frac{60}{16} + \frac{32}{16} = -\frac{1}{16} < 0 \][/tex]
- For [tex]\(x \in (-\frac{2}{3}, \infty)\)[/tex]: Choose [tex]\(x = 0\)[/tex]:
[tex]\[ 3(0)^2 + 5(0) + 2 = 2 > 0 \][/tex]
4. Combine the intervals where the quadratic expression is positive:
From the above analysis:
- [tex]\(3 x^2 + 5 x + 2 > 0\)[/tex] in the intervals [tex]\((-\infty, -1)\)[/tex] and [tex]\((-\frac{2}{3}, \infty)\)[/tex].
5. Write down the solution in interval notation:
[tex]\[ x \in (-\infty, -1) \cup (-\frac{2}{3}, \infty) \][/tex]
6. Identify the corresponding option:
The correct solution matches the first option: [tex]\(x <-1\)[/tex] or [tex]\(x > -\frac{2}{3}\)[/tex].
Thus, the solution to the inequality [tex]\(3 x^2 + 5 x > -2\)[/tex] is:
[tex]\[ x < -1 \text{ or } x > -\frac{2}{3} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.